(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
TNVS is a ride-hailing service that operates on a pre-arranged basis, where the driver approves the commuter’s request. This service is particularly beneficial for Filipinos who do not own cars and rely on well-known modes of transportation used in other countries. Despite the cultural significance of taxis, they have significantly impacted society. Agile methodology is a short-term project management approach that breaks down projects into phases. It involves stakeholders’ ongoing engagement and continuous development at every stage. The team plans, executes, and assesses as they progress through the project. This method helps teams become more efficient and effective, and it is also flexible and adjustable for the project’s development timeline. TNVS Core 2 used this approach to manage their system’s development timeline by dividing the project into two sprints, each lasting 2-3 weeks, to maximize scheduling and organize daily tasks. In summary, TNVS Core 2 utilized agile methodology to ensure timely and organized system completion by dividing it into several phases.